Performance of artificial intelligence in detecting bone fractures in radiographic results: A systematic literature review - Stevany Nurifin (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Artificial intelligence (AI), is currently very widely used in various lines of human life, including in the health sector. In radiology, the role of AI has begun to be involved in the interpretation of radiological imaging results with the aim of making radiological diagnosis more efficient. Purpose: To assess the performance of artificial intelligence in detecting human bone fractures on radiological imaging results. Method: A systematic literature review method using the PUBMED search application with a publication period of the last 5 years using search queries (